for (f+g)(x) you would add up your two function expressions and simplify them
so (f+g)(x) = x/2 + 3x+1
= x/2 + (6x+2)/2 = (7x+2)/2
which is not what you have
suppose we use x=4
f(4)= 4/2 =2
g(4) = 13
so (f+g)(4) = 15
in my (f+g)(x) = (7x+2)/2
(f+g)(4) = (7(4)+2)/2 = 15
for (f-g)(x) you would subtract the two functions,
for (f*g)(x) you would multiply them, etc
test your answers in a similar way to the one I showed you
I have a question, if f(x)=x/2 and g(x)=3x+1 find:
a) (f+g)(x) i know you go x/2+3x+1.
but how do i solve that??
b) (f-g)(x) i know you go x/2-3x+1,
how do i solve?
c)(f*g)(x) how do i solve?
(f/g)(x) how do i solve??
f(g(x)) how do i solve??
thanks for your itmeee
2 answers
thanks so much:)